2020
DOI: 10.3390/agronomy10020155
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Management Strategies of Tillage and No-Tillage Wheat Following Rice in the Yangtze River Basin, China: Grain Yield, Grain Protein, Nitrogen Efficiency, and Economics

Abstract: In the rice-wheat rotation system, conventional culturing of high yield rice results in poor soil conditions and excessive residues, which negatively affect wheat growth. Tillage and nitrogen (N) use are being sought to address this problem. In order to propose a suitable tillage method and corresponding N management strategy, the influence of three tillage methods (i.e., plow tillage followed by rotary tillage (PR), rotary tillage twice (RR), and no-tillage (NT)) and nine forms of N management strategies (i.e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 53 publications
(75 reference statements)
0
6
0
Order By: Relevance
“…In this study, similar results were found; NUpE was higher under zero tillage than under rotary tillage when wheat was planted in harvested rice fields with high soil moisture (Table 6). It has been reported in previous studies that high NUpE is closely related to greater N accumulation, especially high N uptake after anthesis [34][35][36][37][38] . Some reports have indicated that N uptake during the early growth phase is not directly associated with NUpE 37,39,40 .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In this study, similar results were found; NUpE was higher under zero tillage than under rotary tillage when wheat was planted in harvested rice fields with high soil moisture (Table 6). It has been reported in previous studies that high NUpE is closely related to greater N accumulation, especially high N uptake after anthesis [34][35][36][37][38] . Some reports have indicated that N uptake during the early growth phase is not directly associated with NUpE 37,39,40 .…”
Section: Discussionmentioning
confidence: 75%
“…Rial-Lovera et al 33 reported that tillage influenced N use efficiency in a humid growing season. Ding et al 34 found that zero tillage achieved a higher NUpE than tillage under excessive soil moisture conditions during the early growth stage, and that there was no difference when the soil moisture was suitable for tillage. In this study, similar results were found; NUpE was higher under zero tillage than under rotary tillage when wheat was planted in harvested rice fields with high soil moisture (Table 6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wheat production, fertilization and watering strategies are also often considered for quality improvement ( Li et al, 2018 , 2019b ; Yu et al, 2018a , 2021 ). As nitrogen (N) is one of the most important and essential elements for wheat, N fertilizer is usually the most efficient input for simultaneously increasing grain protein content and grain yield in wheat production ( Zebarth et al, 2007 ; Malik et al, 2013 ; Zhen et al, 2018 , 2020 ; Zhong et al, 2018 , 2020 ; Ding et al, 2020 ; Xia et al, 2020 ; Hermans et al, 2021 ; Landolfi et al, 2021 ; Lyu et al, 2021 ; Dong et al, 2022 ; Liu et al, 2022 ; Ma et al, 2022 ). Kichey et al (2007) demonstrated that 50–95% of nitrogen in mature grains is derived from the remobilization of nitrogen stored in the tissues before anthesis.…”
Section: Manipulation Of Fertilization and Watering Regimesmentioning
confidence: 99%
“…Furthermore, a delay of N topdressing was found to alter the grain hardness and flour allergenicity ( Zhong et al, 2019 ). Ding et al (2020) found that an increase in total N provision (210–270 kg ha −1 ) in the Yangtze River basin of China could enhance wheat grain yield, grain protein content, and nitrogen efficiency, with the appropriate topdressing timing and N application dose depending on the environment. Moreover, the biotic and abiotic stresses during wheat growth also significantly affect the quality of wheat ( Duan et al, 2020 ).…”
Section: Manipulation Of Fertilization and Watering Regimesmentioning
confidence: 99%